"Mixed reality" in patient education prior to abdominal aortic aneurysm repair: a prospective, randomized, controlled pilot study - Hatzl, Johannes; Hartmann, Niklas; Böckler, Dittmar; Henning, Daniel; Peters, Andreas; Meisenbacher, Katrin; Uhl, Christian (Vasa, 2023)
Summary:Background: To investigate the usability of Mixed-Reality (MR) during patient education in patients scheduled for abdominal aortic aneurysm (AAA) repair. Patients and methods: Consecutive patients scheduled for elective AAA repair were block-randomized in either the Mixed-Reality group (MR group) or the conventional group (control group). Patients of both groups were educated about open and endovascular repair of their respective AAA. The MR group was educated using a head-mounted display (HMD) demonstrating a three-dimensional virtual reconstruction of the respective patient’s vascular anatomy. The control group was educated using a conventional two-dimensional monitor to display the patient’s vasculature. Outcomes were informational gain as well as patient satisfaction with the educational process. (DRKS-ID: DRKS00025174). Results: 50 patients were included with 25 patients in either group. Both groups demonstrated improvements in scores in the Informational Gain Questionnaire (IGQ) when comparing pre- and post-education scores. (MR group: 6.5 points (±1.8) versus 7.9 points (±1.5); Control group: 6.2 points (±1.8) versus 7.6 points (±1.6); p<0.01) There was no significant difference between the MR group and the control group either in informational gain (MR group: 1.4±1.8; Control group: 1.4±1.8; p=0.5) nor in patient satisfaction scores (MR group: mean 18.3 of maximum 21 points (±3.7); Control group: mean 17 of 21 points (±3.6); p=0.1) Multiple regression revealed no correlation between the use of MR and informational gain or patient satisfaction. Usability of the system was rated high, and patients’ subjective assessment of MR was positive. Conclusions: The use of MR in patient education of AAA patients scheduled for elective repair is feasible. While patients reported positively on the use of MR in education, similar levels of informational gain and patient satisfaction can be achieved with MR and conventional methods.
Gesehen am 04.06.2024
Online veröffentlicht: 9. März 2023